Habitat Connectivity of Fish in Temperate Shallow-Water Seascapes - Perry, Diana; Staveley, Thomas A. B.; Gullström, Martin (Frontiers in Marine Science, 2018)
Movement of organisms comprises a fundamental part of coastal habitat connectivity. Determining the distribution and co-existence of habitat specialists and generalists in shallow-water seascapes leads to a better understanding of the strength of connectivity-driven community patterns in coastal areas. In the current study, unbaited Remote Underwater Video (RUV) systems were used to study habitat usage and connectivity of fish within six shallow-water coastal seascapes on the Swedish west coast. Within each seascape, video sampling was conducted at three different shallow-water habitats: seagrass meadows, rock-macroalgae and unvegetated areas, in June 2014. Comparative analyses showed that the shallow-water fish community was similar in adjacent habitats within a seascape, though abundances of fish were higher within the structurally complex habitats. All habitats were dominated by juveniles, highlighting the importance of the coastal seascape for early fish life stages. The findings demonstrate that adjacent shallow-water habitats in temperate coastal waters are linked through similar species utilization and that the coastal matrix could be regarded in terms of a seascape nursery for fish. The study highlights the importance of considering shallow-water seascape connectivity in coastal conservation planning and management.